CAUTION, PRECAUTION & COMMON SENSE: SOME THOUGHTS ON GMOS, ECOSYSTEMS, AND REGULATING THE UNKNOWN - Cassuto, David N.; Levinson, Drew (Novos Estudos Jurídicos, 2017)
As of 2014, genetically modified crops occupied 448 million acres globally, representing a global market value of 15.7 billion dollars. The United States planted 170 million acres of genetically engineered crops in 2012, including 95% of the nation’s sugar beets, 94% of the soybeans, 90% of the cotton and 88% of the feed corn. While many argue that biotechnology is essential to ensuring long-term food security in the climate change era, little is known of its impact on ecosystems. Potential risks such as changes in adaptive characteristics, gene flow, pest resistance, genotypic or phenotypic instability and adverse effects on non-target organisms must be balanced with the benefits of genetically modified crops. Despite much perseveration about the risks and benefits of GMOs, the United States regulatory regime has remained stagnant, unable to adapt to new innovations in the field. This lack of adequate oversight cannot go on. We propose shifting responsibility to a single agency charged with implementing science-based regulations that embrace the precautionary principle and promote early collaboration among stakeholders, multidisciplinary research, and well-designed monitoring. Part I of this Article provides an overview of biotechnology in modern agriculture. More specifically, it evaluates potential benefits and risks associated with genetically modified crops. Part II outlines the United States regulatory regime as it applies to genetically modified crops. Part III analyzes the current regulatory process, focusing specifically on the Department of Agriculture’s ineffective role in the environmental review process. Last, Part IV offers several potential adjustments to improve our ability to identify and mitigate the unforeseeable consequences of implementing this revolutionary technology.